Shaping Energy-Saving Behavior in Education System: A Systematic Review - Irmak, Alettin; Kurmanov, Nurlan; Zhadigerova, Onaikhan; Turdiyeva, Zukhra; Bakirbekova, Aigul; Saimagambetova, Gaukhar; Baidakov, Assilbek; Mukhamejanova, Aigul; Tolysbayeva, Madina; Seitzhanov, Sagyngali (International Journal of Energy Economics and Policy, 2023)
Shaping energy-saving behavior in education system plays huge and obvious role in economic and social development. While there is a large amount of literature covering the issues of technical advancements in implementation of energy-saving technologies, organizational and technical aspects of world experience, there is still a lack of publications exploring the scale and features of energy-saving behavior in education system. This paper analyzes features of shaping energy-saving behavior at three levels: school, university, and communities. It systematically reviews 119 WoS and Scopus studies, which allowed us to determine influence factors and prospects of shaping energy-saving behavior for the younger generation and community reps. The paper sets four research questions aimed at data analysis. The results showed (a) the lack of research on issues related to shaping of energy-saving behavior at the school and university levels; (b) that mainly, literature focuses on a comprehensive study of individual and socio-demographic factors affecting energy-saving behavior of communities; (c) that at the university and school levels, situational and individual factors have the greatest impact on energy-saving behavior of students; gaps in socio-demographic factor research; and d) as prospects of shaping energy-saving behavior of students, development of educational programs, implementation of state policy on energy conservation, information on energy conservation issues can be highlighted – all from the beginning of the COVID-19 pandemic to the present. The paper is intended for researchers, education and energy experts interested in possibilities of educational technologies in shaping energy-saving behavior.